Pemberdayaan Masyarakat Melalui Pelatihan Membuat Kerupuk Gendar di Sekelimus Utara Kota Bandung - Revita Yanuarsari (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2015)
Community empowerment is a development process where community initiate to start the process of social activities to improve the situation and condition their self. Community empowerment can happen only if citizens participate. Based on that, the training was held community empowerment through training in the manufacture of “kerupuk gendar” Sekelimus Utara Bandung. This training is expected to bring a positive influence for the citizens of Sekelimus Utara Bandung, especially for mothers. The training process was conducted on the learning theory and practice. Selection of “kerupuk gendar” as the main object of this training as “kerupuk gendar” is one of the traditional food preparation easy and not costly. Traditional foods are foods and beverages commonly consumed by a particular community, with a distinctive flavor that is accepted by the community. As we know that food is not only serves to satisfying their hunger alone but the food has a social function, culture, politics, and economics. Various types of food produced a nation can be used as one measure of the high culture of the people concerned. The food not only as a means to satisfy hunger, maintain relationships, but can also be sold, promoted resulting in a slight advantage. After this training is expected that residents can obtain various benefits include improving knowledge and skills, increase opportunities for entrepreneurship, increase revenue, improve public participation and to partner.